Implementation of The Madrasah Exam Using The TC-Exam Application At MTSN 1 Palangka Raya - Maulana, Daniel; Rohmadi, Mukhlis; Rizal, Setria Utama (Institut Agama Islam Negeri Sorong, 2021)
This study is based on the problem of madrasah exams that cannot be conducted directly or in writing due to the impact of covid-19 which requires the implementation of madrasah exams to be conducted online. So that madrasah exams are conducted online using TCExam application conducted in MTsN 1 Palangka Raya and what obstacles occur and how the implementation of madrasah exams using the TCExam application is specifically on madrasah exams in the religious field studied. The purpose of this research is to describe the planning of madrasah exam implementation using TCExam application in the religious field, constraints in the implementation of madrasah exams using TCExam application in the religious field and students' response to the implementation of madrasah exams using the TCExam application. The research used in this study is descriptive qualitative research. The place of this research is MTsN 1 Palangka Raya. The subjects of this study were the Head of Madrasah, Wakamad curriculum, Operator, and Teacher of Religious Affairs. Data collection using interview techniques and documentation. Data analysis is done by collecting data, presenting and drawing conclusions. The validity of the data is done using triangulation of sources and techniques. The results of this study show that 1. Planning the implementation of madrasah exams using TCExam application in the field of religion in MTsN 1 Palangka Raya, namely the simulation and explanation from the operator to teachers for the use of TCExam application. 2. Implementation of madrasah exams using TCExam application. 3. Constraints in the implementation of madrasah exams using tcexam application in the field of religion in MTsN 1 Palangka Raya namely in students who are sometimes late to log in madrasah exams using the TCExam application, further constraints in the internet network of students are unstable and also in the implementation of madrasah exams using the online TCExam application is another obstacle also that students can commit fraud or cheating in this case the role of parents is very important to supervise students in the implementation of online madrasah exams using the TCExam application.